The Protocol of Fixed Reconstruction for Severely Worn Teeth Combined with Anterior Deep Bite - Ya-Wen Zhao; Rong Gao; Hui-Qiang Sun (Case Reports in Dentistry)
Full mouth reconstruction is one of the most effective methods to restore severe worn teeth that have suffered reduced vertical dimension. Although the use of the overlay splint restoration for a trial period allowing the patient to adapt to an increased vertical dimension is the recognized method, the specific protocol from the transitional splint to the fixed reconstruction is yet to be established. This case report describes a 50-year-old female patient who has severely worn teeth combined with an anterior deep bite and chewing pain. The protocol of the treatment process is described.